Primary cutaneous CD30+ lymphoproliferative disorder – a 10-year follow-up. A case report and differential diagnosis - Szpor, Joanna; Dyduch, Grzegorz; Gałązka, Krystyna; Bahyrycz, Jan; Stój, Anastazja; Tomaszewska, Romana (Polish Journal of Pathology, 2009)
Primary cutaneous CD30+ lymphoproliferative disorders (LPDs) are the second most common group of primary cutaneous T-cell lymphomas (CTCLs). The spectrum of LPDs includes lymphomatoid papulosis (LyP), primary cutaneous anaplastic large cell lymphoma (C-ALCL) and borderline cases. The term “borderline lesions” refers to cases where histological features are similar to LyP, but clinically behave as C-ALCL, or to cases where histological features are typical for C-ALCL, but clinically behave as LyP. We present a clinical and morphological picture of LPD in a 57-year old patient treated in the Department of Oncology and of a relapse after ten years of follow-up and discuss clinical and morphological differential diagnosis and the significance of such diagnosis